ORGANIZM (European Science Methodical Journal, 2026)
In this article, the concept of an organism and its connection with natural geographical complexes are analyzed from a scientific point of view. Issues of the main characteristics of the organism, systematicity, integrity, and interrelationships between components are highlighted. It also explains the formation of natural geographical complexes as a single system based on the interaction of natural components - climate, relief, soil, water, flora, and fauna. Based on the scientific views of Shubaev and Baratov, the article discusses the development of natural systems, the exchange of matter and energy, and the impact of human activity on nature. The necessity of maintaining the natural balance and nature conservation is also substantiated.